Programmed Cell Death Receptor (PD-1) Ligand (PD-L1) expression in Philadelphia chromosome-negative myeloproliferative neoplasms. (April 2019) - Wang, Jen-Chin; Chen, Chi; Kundra, Ajay; Kodali, Sreenath; Pandey, Anita; Wong, Ching; Cheung, Tony; Gotlieb, Vladimir; Joseph, Gardith; Tribie, Sophia
Highlights: This is the largest and first cohort study of PD-1, PD-L1 in Ph (-) MPN patients. PD-1, PD-L1 are increased in ET, PV, and MF when they grouped as MPN than controls. Positive expression (>50%) of PD-1, PD-L1 in 20% in CD34+ cells, Low in other cells. No correlation between PD-1, PD-L1 levels and other clinical features (JAK2 etc). Abstract: Programmed Cell Death Receptor (PD-1) and its Ligand (PD-L1) pathway inhibitor therapy has been explored in the field of oncology treatment mainly for solid tumors. In hematologic malignancies, there is limited information except for Hodgkin's lymphoma, and there is even less information regarding myeloproliferative neoplasm (MPN). Therefore, we explored this by first measuring PD-1 and PD-L1 levels (percentage of positive cells) in 63 patients with Philadelphia chromosome-negative MPN ( Ph(-) MPN), including 16 MF (12 PMF, 2 post-PV-MF, 2 post-ET-MF), 29 ET, and 18 PV. We found there was no significant difference in PD-1 or PD-L1 levels between the different MPN groups but that there was a significant difference when PV, ET and MF were grouped as MPN and compared with controls, of all immune cells including CD4 +, CD8 +, CD14 + and CD34 + progenitor cells. We further found a higher incidence of higher expression levels (more than 50% of cells with positive expression) of PD-1 and PD-L1 (20% and 26%, respectively) in the CD34 + cells; in contrast, we found a low incidence (0.08–1.8%) in the immune cells in MPN patients. PD-1 and PD-L1 levels were also measured by MFI methods, and we obtained similar results except the measurements by percentage appeared to be more sensitive than the MFI methods. We found no correlation between PD-1 and PD-L1 expression levels and clinical features including WBC, platelet counts, hemoglobin levels, presence or absence of the JAK2, MPL, or CALR gene mutation, or splenomegaly. Since MPN represents stem cell disorders, the presence of elevated expression of PD-1 and PD-L1 in these cells suggests that the exploration of PD-1 and PD-L1 pathway inhibitor therapy may be worthwhile in Ph(-) MPN.